Pendidikan Karakter Dalam Al-Qur’an Surat Lukman Ayat 12-19 - hazrullah, hazrullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Character education in the Qur'an is an important aspect that emphasizes the development of spiritual, moral and ethical values in social life. The Qur'an contains teachings that aim to form pious, intelligent, moral, noble, responsible and high-quality individuals. Character education in Surah Lukman verses 12 to 19 relates to the importance of teaching spiritual values, noble morals and responsibility to children from an early age. This surah contains Lukman's advice to his children regarding the oneness of Allah SWT, the obligation to do good, be filial to both parents, by prioritizing values such as gratitude, wisdom, respect, piety, honesty, trust, compassion, gentleness, love, responsibility. responsible, good character, good manners, humility, patience, and simplicity. These values are the basis for forming good character for children and are expected to help children grow and develop into individuals who are pious, intelligent, have noble character, are of good quality and are able to face life's challenges in the future